Response to comment by Guerra et al. - Xinyue Yang; Yan Cheng; Guanfang Su (Bioscience Reports, 2018)
This is a response by the authors of the review article ‘A review of the multifunctionality of angiopoietin-like 4 in eye disease’ [Biosci. Rep. (2018) 38, BSR20180557, https://doi.org/10.1042/BSR20180557] to the comment published in this issue by Guerra et al. [Biosci. Rep. (2018) 38, BSR20180557, https://doi.org/10.1042/BSR20181462]